Shaping Future Success: Evidence from an Early Childhood Human Capital Formation Intervention - Deepak Saraswat; Shwetlena Sabarwal; Lindsey Lacey; Natasha Jha; Nishith Prakash; Rachel Cohen (Institute of Labor Economics (IZA), 2025)
Nearly 200 million children under five in low- and middle-income countries face developmental deficits despite growing access to early childhood services. We report evidence from a randomized controlled trial (N=3,131 children in 201 schools) in Nepal's government system that tested three models combining classroom quality with parental engagement. All teachers received a 15-day training on pedagogy, standards, and caregiver outreach, after which schools were randomly assigned to models where caregiver sessions were led by teachers alone, teachers supported with in-class helpers, or external facilitators. The program raised children's developmental outcomes by 0.10–0.20 standard deviations and improved caregiver engagement by similar magnitudes, with strongest effects when teachers received support that preserved classroom quality while engaging families. Gains were concentrated among disadvantaged households, underscoring the potential to reduce early inequalities. Mechanism analysis shows that the program shifted home and school inputs from substitutes to complements, creating reinforcing pathways for child development.
Keywords: J13; J24; I21; I24; O15; 330; early childhood development; cognitive skills; non-cognitive skills; Ages and Stages Questionnaire (ASQ); Nepal